Analisis Supply-Demand Energi Listrik Untuk Memenuhi Kebutuhan PLN Sulawesi Selatan - Asmiani, Nur (CV Insight Publisher, 2024)
Electrical energy is one of the basic needs in modern human life. Electricity is very integrated into everyday life, work, or commercial. Indonesian society, urban, already depend on electric energy to run everyday life. The purpose of this study to determine the level of electricity consumption in South Sulawesi and to determine selling value of energy demand to PLN. Stages and research methods undertaken consist of the process stages of research, methods of data retrieval, data processing and stages of data analysis, and the stage of report generation. The data taken are primary data and secondary data, after the data collected data are analyzed to calculate the supply-demand of electrical energy needed by PLN. The composition of electricity demand in the base year (2013) consists of Commercial sector 999,485.90 MWH, industrial sector 859,482.75 MWH, government sector 248,237.97 MWH, social sector 202,789.65 MWH and household sector with 2,568,038,85 MWH. For the year 2015 also still dominated by the household sector with 2,568,038.85 MWH. This figure is the same from 2013. Likewise with the commercial sector which rose to 1,011,709.57 MWH and industrial sector to 861,117.44 MWH. government sector to 249,256.10 MWH and social sector to 204,689.38 MWH. To be able to meet the needs of electrical energy in South Sulawesi, is expected with the power plant PLTU PT. Bosowa Jeneponto Energy with total power generated of 128,877.37 MWH can supply electrical energy for PLN South and West Sulawesi in fulfilling the needs of 100 MW electricity energy every year for new customers, with the selling price of PLTU power plant PT. Bosowa Energy to PLN Rp 500 / Kwh.